When the mask slips: A peripheral T-cell lymphoma disguised as lupus with myelofibrosis in a patient with May-Hegglin syndrome - V Da Silva Constante; H Couvert; A Wolfromm; M Ilzkovitz (Leukemia Research Reports)
We describe the case of a female patient with May-Hegglin syndrome who developed peripheral T-cell lymphoma not otherwise specified. The patient presents with systemic lupus erythematous phenotype and myelofibrosis secondary to T-cell lymphoma. Peripheral T-cell lymphoma not otherwise specified, represents 25 % of all peripheral T-cell lymphoma. Its diagnosis remains challenging due to the polymorphous clinical presentation and pathological heterogeneity. Myelofibrosis associated with malignant lymphomas is rare and peripheral T-cell lymphoma is even rarer. To our knowledge, this is the first case to describe an association between May-Hegglin syndrome and a peripheral T-cell lymphoma.